Influence of Turbulence Models on Three-Dimensional Numerical Simulation of Downpull Phenomenon under Vertical Lift Gates - Zhe, Khor Hao; Tion, Puay How (International Journal on Engineering Technology and Infrastructure Development, 2024)
One of the key concerns when operating a vertical lift gate is the underestimation of hydrodynamic downpull forces. Computational Fluid Dynamics (CFD) is an effective method in simulating downpull phenomenon under vertical lift gates. The purpose of this study is to investigate the effect of turbulence models on the numerical simulation of downpull phenomenon under vertical lift gates using Flow-3D®, a commercial CFD software. The downpull phenomenon is simulated using three different turbulence models, which are standard k-ε model, k-ω two-equation model and LES model. The simulations are done for nine different gate opening sizes using the three aforementioned turbulence models. The setup of numerical model is identical to experiment setup used by Naudascher in 1964. The results showed that standard k-ε model showed the least deviation from experimental results with an average percentage error of 11.365%.